Peroxisome Proliferator-Activated Receptor Delta Agonist (PPAR- δ) and Selective Androgen Receptor Modulator (SARM) Abuse: Clinical, Analytical and Biological Data in a Case Involving a Poisonous Combination of GW1516 (Cardarine) and MK2866 (Ostarine) - Pascal Kintz; Laurie Gheddar; Camille Paradis; Mickael Chinellato; Alice Ameline; Jean-Sébastien Raul; Magali Oliva-Labadie (Toxics, 2021)
A 43-year-old male, sport coach, presented him-self at the Emergency unit of a local hospital for epigastric pain, myalgia pain and severe headache. He claimed having used for some days a combination of GW1516 (cardarine), a peroxisome proliferator-activated receptor delta agonist (PPAR- δ) and MK2866 (ostarine), a selective androgen receptor modulator (SARM) to gain skeletal muscles. Cytolysis with marked increase of alanine aminotransferase or ALT (up to 922 UI/L) and aspartate aminotransferase or AST (up to 2558 UI/L) and massive rhabdomyolysis with elevated creatine phosphokinase or CPK (up to 86435 UI/L) were the main unusual biochemistry parameters. Using a specific liquid chromatography coupled to tandem mass spectrometry method, cardarine and ostarine tested positive in blood at 403 and 1 ng/mL, respectively. In urine, due to extensive metabolism, the parent GW1516 was not identified, while ostarine was at 88 ng/mL. Finally, both drugs were identified in hair (2 cm in length, brown in colour), at 146 and 1105 pg/mg for cardarine and ostarine, respectively. This clearly demonstrates repetitive abuse over the last 2 months. Asthenia was persistent for 2 weeks and 6 weeks after the admission, the subject fully recovered.